An evaluation of a new tool to aid judgements of credibility in the medico-legal setting - Akehurst, Lucy (Legal and criminological psychology, 2017)
Purpose. Clinical psychologists and other health professionals are often requested to act as expert witnesses in Court. They are required to assess, and report upon, the reliability of the accounts of physical and psychological symptoms made by their clients. This study investigated the effectiveness of a checklist drawing upon relevant literature on lying and malingering to aid the detection of exaggeration of physical symptoms. Method. Sixty-four participants were cast as interviewers and assigned to either a ‘checklist’ or ‘no checklist’ condition. Another 64 volunteers were assigned to either a ‘truth teller’ or ‘malingerer’ role and, after undergoing a cold pressor procedure, were interviewed about their experience. The interviewers with a checklist drawn from the literature were asked to rate the presence of 28 checklist items on 5-point Likert scales and to indicate whether or not they believed their interviewee was truthful or exaggerating his or her symptoms. The interviewers without the checklist were asked to simply indicate whether their interviewee was truthful or exaggerating. Results. Evaluators who were not given the checklist did not classify their interviewees at a level significantly better than chance. Those using the checklist achieved an overall hit rate of 70%. Signal detection analysis supported the finding that those with the checklist showed greater discriminability. Nine checklist items significantly discriminated between truth tellers and malingerers. Furthermore, the total checklist score was significantly higher for exaggerated accounts than for truthful accounts. Conclusions. Results suggest that a checklist based on the literatures into lying and malingering warrants further investigation. Such a tool would be useful as an aid for expert witnesses called to provide informed opinion on the likelihood that a claimant is exaggerating, malingering or otherwise misrepresenting difficulties.